Comparison of early (EOP) and late onset psoriasis (LOP) regarding systemic inflammatory comorbidities: LOP is a more rapid subtype of psoriasis - Huseynova Terzi, Leyla; Dogan Gunaydin, Sibel (Dermatology Practical & Conceptual, 2022)
Background: Early onset psoriasis (EOP) and late onset psoriasis (LOP) differs regarding genetic background, clinical presentation, and course of disease.Objective: In this study, comparison of EOP and LOP regarding systemic inflammatory comorbidities which are frequently seen in psoriasis and determination of possible differences is aimed.Methods: A total of 160 plaque psoriasis patients; 121 with EOP and 39 with LOP were enrolled for the study. Data was collected with face-to-face questionnaire and patients’ medical chart evaluation. Collected data included medical and family history, clinical features and parameters indicating severity of psoriasis, results of laboratory work-up, physical and dermatological examination findings, presence of joint and nail involvement and associated inflammatory systemic comorbidities such as cardiovascular diseases (CVD), diabetes mellitus (DM), hypertension (HT), metabolic syndrome (MS), obesity.Results: Nail involvement and PsA occurred more rapidly in LOP compared to EOP (p<0.01, p<0.01). Compared frequencies in LOP and EOP were 7.7% vs 0.8% for CVD, 38.5% vs 14% for HT, 33.3% vs 9.9% for DM and 44.7% vs 24.8% for MS respectively. CVD, HT, DM and MS were significantly more frequent in LOP compared to EOP (p=0.045, p=0.001, p<0.01, p=0.022). Results of multivariate analysis performed taking into account the age, gender, severity parameters of disease, alcohol consumption, smoking habits, and other concurrent systemic comorbidities revealed LOP to be an independent risk factor for CVD and DM (p<0.01, R2: 0.036, p<0.01, R2: 0.077). Conclusion: LOP seems to interact with systemic comorbidities hence generating more severe inflammatory burden and shows a more rapid course.